Analisis Miskonsepsi Buku Teks Pelajaran Biologi Kelas XI Semester 1 SMAN di Kota Banda Aceh - Nurul Fajriana; Abdullah Abdullah; Safrida Safrida (Universitas Islam Negeri Ar-Raniry, 2016)
This study was designed to identify the misconceptions in biology textbooks of class XI used by the students of senior high school in Banda Aceh. The method used was descriptive method. The instrument used was observation sheet. The results showed that the Biology textbooks used by the students have some misconceptions. The highest misconceptions was found in the topic of skeletal system (27%), circulatory system (25%) and the lowest one was found in the topic of cell (9%).